Добросовісність заволодіння майном як умова набувальної давності - Чубоха, Н.; Chubokha, N. (Східноєвропейський національний університет імені Лесі Українки, 2016)
Стаття присвячена висвітленню добросовісності як принципу цивільного права і добросовісності заволодіння майном як умови набувальної давності. Проаналізовано підходи різних вчених щодо змісту та значення добросовісності як морального принципу, якості, яка притаманна поведінці суб’єктів цивільного права і як умови набувальної давності. The article is devoted to the interpretation of theessence and content of good faith as a principle of civil law and integrity as the principal acquisitive prescription condition. The study offers insights into the approaches of different scholars to the role, content and meaning of «good faith», who consider this notion as a moral principle, or the quality of the behavior of the subject of civil rights and as a condition of the acquisitive prescription. The author emphasizes the need for the wording of the concept of good faith as a single universal term for all private relations to ensure its applicability in all spheres of civil law. It has been determined that the integrity of taking possession of property implies the two conditions of the acquisitive prescription: good faith of a possessor (bona fides) and legal entitlement to the property (justus titulus), which are particularly important at the moment of taking possession of the property (transfer of items).
Integrity of the Possession by Propertyas a Condition of Acquisitive Prescription
Keywords: добросовісність; цивільне право; принцип цивільного права; цивільні правовідносини; набувальна давність; добросовісність; заволодіння; майно; строк; рецепція; власник; набувач; good faith/integrity; civil law; the principle of civil law; civil matters; acquisitive prescription; acquisition; property; term; reception; the owner; purchaser/transferee